Sistematica del Falco pellegrino (Falco peregrinus) in Italia - Sara' M (Edizioni Belvedere, 2021)
Validated data and published studies indicate that four subspecies are present in continental Italy and its surrounding islands. Two of these subspecies (F. p. peregrinus and F. p. brookei) represent breeding populations, while the other two (F. p. calidus and F. p. pelegrinoides) winter and migrate in the country. Indeed, the European subspecies (F. p. peregrinus) has the most intriguing status, as it can both breed and winter. The exact range of the breeding population is not well-defined - it probably occurs in alpine and pre-alpine areas, perhaps reaching the Apennines of central Italy. Individuals originating from northern European countries in autumn and winter certainly implement this breeding population, as shown by ringing recoveries. In southern Italy the range of the breeding European peregrine is complementary or intergrades with that of the Mediterranean subspecies (F. p. brookei), which is present also in Sicily and Sardinia. A genetic investigation of a sample of Italian individuals showed new distinct Sicilian haplotypes, nonetheless the overall allelic patterns and genetic structuring of microsatellites were similar to those of other European populations. Regarding the other two subspecies: the Barbary Falcon’s (F. p. pelegrinoides) presence in Italy is purely accidental. The Siberian Tundra Peregrine (F. p. calidus), instead, is a regular wintering visitor in several regions of the country; several observations occur every year, and these have been increasing recently, due to a growing number of amateur and professional birdwatchers.